Adaptation of the Areas of Worklife Survey C. Masłach and M. Leitera - Terelak, Jan Felicjan; Izwantowska, Anna (Studia Psychologica: Theoria et praxis, 2009)
Work moves cultural adaptation The Areas the of Worklife Survey C. Masłach and M. Leitera, measuring five of organizational factors: the workload , feeling of control in work (the autonomy); perceived the support of organization (the prize and sense of justice), the social support in work as well as congruence of the worker and organizations value.